Restauración y puesta en valor de la cuarta casona de la plaza Dos de Mayo - Celis Estrada, Diego Javier (2021)
The construction of Dos de Mayo’s Square, at the end of the 19th century, was the beginning of a new idea of a city in Peru. The viceregal idea of the city was forgotten, the walls were demolished and the modernization of the city of Lima was proposed. It is in this context that the eight buildings that make up the square were built. They were also the result of a new building idea in which the viceregal idea of a house-patio was replaced by an architecture of French influence. In conclusion, it can be said that the square and its eight buildings marked a milestone in architecture and urban planning in Peru. At present, these important buildings are in terrible condition, especially the 4th building, which suffered a fire in 2014. For this reason, this project proposes its restoration and conservation.